BUSINESS HEALTHY IN COMPETITION OF PARTNERSHIP - Andi Tira (Indonesia Prime, 2016)
The principles of economic democracy broke through the overall activities of the society and the State, which sectors of the economy who undertakes by the Constitution as the Foundation of the constitutional business activities in pursuit of national development goals, and is the nation's commitment to the partnership philosophy as well as for businessmen. Although the philosophy of partnership so ideal, but when economic growth is uneven, then it will cause the distance (social inequality) between the powerful rich with the small weak Agreement are build oligopoly if the offender attempts to make agreements with other businessmen to do production and mastery or marketing goods and or services that could result in a monopoly or competition is not healthy